The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Irritable Bowel Syndrome - Novel Concepts for Research and Treatment 2016
DOI: 10.5772/66301
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidities in Irritable Bowel Syndrome (IBS)

Abstract: F" lot of research has pointed out that irritable bowel syndrome (I"S is a multifactorial illness involving visceral hypersensitivity, alteration of communication between the enteric nervous system (ENS and central nervous system (CNS , increased intestinal permeability, minimal intestinal inlammation, and altered intestinal microlora. Psychological, social, and genetic factors appear to be important in the development of I"S symptomatology through several mechanisms. This chapter addresses the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Long-term effects on exposure to stress in early life have shown epigenetic changes. [ 15 ] The most common physical comorbidity was diabetes mellitus (37.8%). A study comparing the prevalence of diabetes mellitus in patients with IBS and healthy controls showed that the incidence of DM is significantly higher in IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term effects on exposure to stress in early life have shown epigenetic changes. [ 15 ] The most common physical comorbidity was diabetes mellitus (37.8%). A study comparing the prevalence of diabetes mellitus in patients with IBS and healthy controls showed that the incidence of DM is significantly higher in IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Roy conducted over 366 healthy control females age between 35-50 years [mean age(41.49±3.80)] found psychiatric morbidities about 28.1% among which major depressive disorder (11.2%) followed by generalized anxiety disorder (9.8%), obsessive compulsive disorder (2.7%), panic disorder (1.6%), somatization disorder (1.6%) and conversion disorder (1.1%) 12. Another study conducted in same place by Khan over 110 healthy controls age between 18-60 years (majority 45.5% of age 18-30) and found psychiatric morbidities about 16.4 % among which major depressive disorder 8.2 %, anxiety disorder 4.5 5 and somatization disorder 3.6 % 13. …”
mentioning
confidence: 95%